2008
DOI: 10.1182/asheducation-2008.1.359
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Zone Lymphomas: Management of Nodal, Splenic, and MALT NHL

Abstract: Marginal zone lymphomas are indolent B-cell lymphomas that originate from the marginal zone of B-cell follicles. For several subtypes, the initiation of disease appears to be a consequence of chronic infection and/ or inflammation. While the initial lymphoid hyperplasia is driven by physiologic antigenic stimulation, additional oncogenic events, such as chromosomal translocations leading to constitutive activation of signaling pathways, occur during the progression of disease that ultimately result in antigen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 42 publications
0
53
0
2
Order By: Relevance
“…Usually, guidelines for follicular lymphoma or chronic lymphocytic leukemia/ small lymphocytic lymphoma are adopted. 99 Different studies have reported different (combinations of) treatments, including watchful waiting, surgery, radiotherapy, different chemotherapeutic regimens, rituximab, and autologous stem cell transplantation. 9,[13][14][15][16][17][18][19] However, no optimal treatment strategy can be deduced from these studies.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…Usually, guidelines for follicular lymphoma or chronic lymphocytic leukemia/ small lymphocytic lymphoma are adopted. 99 Different studies have reported different (combinations of) treatments, including watchful waiting, surgery, radiotherapy, different chemotherapeutic regimens, rituximab, and autologous stem cell transplantation. 9,[13][14][15][16][17][18][19] However, no optimal treatment strategy can be deduced from these studies.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…Inmunofenotípicamente expresan CD19,CD20,CD22 y PAX5 y no expresan CD25 y CD103, lo que ayuda a diferenciarlo de la tricoleucemia 15,16 . En esta paciente, si se hubiera podido contar con la determinación del inmunofenotipo en la primera hospitalización, se habría conocido el tipo específi co de linfoma que padecía, lo que hubiera permitido haber iniciado su terapia un año antes, evitando la complicación que motivó la comunicación de este caso.…”
Section: Discussionunclassified
“…La esplenectomía es la terapia de elección ya que corrige las citopenias, alivia los síntomas y cuando ello no es sufi ciente se ha usado quimioterapia (fl udarabina, pentostatin). En ancianos o pacientes con falla renal se ha utilizado rituximab con buenos resultados 15,16,28,29 .…”
Section: Discussionunclassified
“…The optimal management of extranodal marginal zone B-cell lymphomas has not yet been clearly defined, especially in H. pylori-negative MALT lymphomas and refractory B-cell lymphomas (1,7). Although chemotherapy with CHOP may not be an optimal regimen, it is the standard treatment for patients with aggressive lymphomas (9).…”
Section: Discussionmentioning
confidence: 99%